McMurdo Dry Valleys McMurdo Dry Valleys Lake Levels - Doran, Peter (Environmental Data Initiative, 2018)
Lake Level measurements are carried out each austral summer season for the lakes in the McMurdo Dry Valleys, Antarctica.